Look for me : a novel - Gardner, Lisa (New York: Dutton, 2018)
"In #1 New York Times bestselling author Lisa Gardner's latest twisty thrill ride, Detective D. D. Warren and Find Her's Flora Dane return in a race against the clock to either save a young girl's life. or bring her to justice. The home of a family of five is now a crime scene: four of them savagely murdered, one--a sixteen-year-old girl--missing. Was she lucky to have escaped? Or is her absence evidence of something sinister? Detective D. D. Warren is on the case--but so is survivor-turned-avenger Flora Dane. Seeking different types of justice, they must make sense of the clues left behind by a young woman who, whether as victim or suspect, is silently pleading, Look for me"--
Keywords: Murder -- Investigation -- Fiction; FICTION / Suspense; FICTION / Mystery & Detective / Police Procedural; Suspense fiction; Mystery fiction